2022
DOI: 10.3847/1538-4357/ac7a40
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Inner Parsec of the Blazar J1924–2914 with the Event Horizon Telescope

Abstract: The blazar J1924–2914 is a primary Event Horizon Telescope (EHT) calibrator for the Galactic center’s black hole Sagittarius A*. Here we present the first total and linearly polarized intensity images of this source obtained with the unprecedented 20 μas resolution of the EHT. J1924–2914 is a very compact flat-spectrum radio source with strong optical variability and polarization. In April 2017 the source was observed quasi-simultaneously with the EHT (April 5–11), the Global Millimeter VLBI Array (April 3), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 80 publications
0
34
0
Order By: Relevance
“…Measurements on baselines longer than 2.5 Gλ indicate a deviation from the Gaussian model, in agreement with the resolved source consisting of more than one component. Both EHT Sgr A * calibrators, NRAO 530 and J1924-2914 (Issaoun et al 2022) are fairly compact and bright sources at 230 GHz. During the week-long EHT observing run, their source structure and flux density did not show significant variations (see Figure 3).…”
Section: Observations and Data Calibrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurements on baselines longer than 2.5 Gλ indicate a deviation from the Gaussian model, in agreement with the resolved source consisting of more than one component. Both EHT Sgr A * calibrators, NRAO 530 and J1924-2914 (Issaoun et al 2022) are fairly compact and bright sources at 230 GHz. During the week-long EHT observing run, their source structure and flux density did not show significant variations (see Figure 3).…”
Section: Observations and Data Calibrationmentioning
confidence: 99%
“…The polarimetric leakage calibration follows procedures outlined in EHTC et al (2021), where D-terms of stations with an intra-site VLBI baseline (ALMA, APEX, SMA, and JCMT) were calculated through a multisource fitting procedure (Martí-Vidal et al 2021), and several estimates for D-terms of remaining stations were reported. Here we employ the fiducial D-terms given by Issaoun et al (2022) based on the analysis presented in EHTC et al (2021). Some imaging algorithms that we use ignore the leakage calibration and estimate D-terms independently, providing an additional consistency check of the calibration procedures and their impact on the resulting images (see Section 3).…”
Section: Observations and Data Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…They can be easily incorporated into global MHD simulations of jet launching and propagation, to identify KH-unstable surfaces [19,34,35]. On the observational side, claims have been made that the KHI is observed along Active Galactic Nuclei (AGN) jets, based on the geometry of the outflow [36,37]. Our formulae can place this claim on solid grounds, if estimates of the field strength and orientation and of the flow velocities are available.…”
mentioning
confidence: 99%